2001
DOI: 10.1182/blood.v98.2.486
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of BCL-2/JH translocation in peripheral blood lymphocytes of healthy Japanese individuals

Abstract: The incidence of follicular lymphoma differs significantly between white and Japanese individuals. Translocation between the BCL-2 and immunoglobulin heavy chain genes is detected in 85% to 90% of all follicular lymphomas in whites. Recently, BCL-2/J H translocation was detected in peripheral blood lymphocytes from more than 50% of healthy white individuals. To clarify the reason for the difference in incidence of follicular lymphoma between whites and Japanese, the frequency of BCL-2/J H translocation in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 19 publications
5
51
0
Order By: Relevance
“…The frequency of the t(14;18) -positive lymphocytes with more than 10 copies detected in healthy Chinese individuals (55%) was similar to previous frequencies reported for Caucasian populations ( 15 , 34 ) and higher than that reported for Japanese individuals (16%) ( 34 ). The Chinese have a similarly lower level of lymphoma as the Japanese in comparison to Western Caucasian populations.…”
Section: Downloaded Fromsupporting
confidence: 85%
“…The frequency of the t(14;18) -positive lymphocytes with more than 10 copies detected in healthy Chinese individuals (55%) was similar to previous frequencies reported for Caucasian populations ( 15 , 34 ) and higher than that reported for Japanese individuals (16%) ( 34 ). The Chinese have a similarly lower level of lymphoma as the Japanese in comparison to Western Caucasian populations.…”
Section: Downloaded Fromsupporting
confidence: 85%
“…7,9,10,12 All sequenced PCR products contained a fragment of the 5Ј BCL-2 (MBR) locus and 1 of the 6 3Ј-J H regions, separated by an inserted sequence of varying length probably resulting from illegitimate V(D)J recombination (Table I). 17 Although there are some discrepancies, the BCL-2 breakpoints tended to fall into 3 clusters regions: bp 3055, 3115 and 3165 (less frequently) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Occurring in 85% of human follicular lymphoma and in 20% of diffuse large cell lymphoma, 6 it is also present in peripheral blood lymphocytes of healthy individuals. [7][8][9][10][11][12] Before studying the effect of pesticide exposure among farmers, it is necessary to evaluate the influence of potential confounding factors. Pesticide use follows a temporal cycle with potential effects on biomarkers of season-related environmental factors.…”
mentioning
confidence: 99%
“…The reported mean prevalence of t(14;18) in peripheral blood of healthy individuals is 36%, ranging from 8 to 100%, depending on the sensitivity of the PCR assays used to detect t(14;18). [4][5][6][7][8][9] In our study, quantitative levels of t(14;18) in healthy donors were low (o0.01%). This finding also correlates well with other studies that have shown a low quantity of cells carrying t(14;18) in individuals without FL.…”
Section: Discussionmentioning
confidence: 72%
“…3 Although this translocation is classically associated with FL, many studies have reported the presence of t(14;18) in healthy individuals who do not have FL. [4][5][6][7][8][9][10][11] Allogeneic stem cell transplantation (allo-SCT) is of increasing interest as a therapeutic option for patients due to the potential of a graft-versus-lymphoma effect to provide long-term disease control. [12][13][14][15] We have recently reported that monitoring the tumor load of t(14;18) cells by real-time quantitative PCR (RQ-PCR) may predict the outcome of FL patients after allo-SCT.…”
Section: Pcrmentioning
confidence: 99%